2006
DOI: 10.1021/es051335p
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Effect of Aerobic Biodegradation on Soil Vapor Intrusion into Buildings:  Influence of Degradation Rate, Source Concentration, and Depth

Abstract: Steady-state vapor intrusion scenarios involving aerobically biodegradable chemicals are studied using a three-dimensional multicomponent numerical model. In these scenarios, sources of aerobically biodegradable chemical vapors are placed at depths of 1-14 m beneath a 10 m x 10 m basement or slab-on-grade construction building, and the simultaneous transport and reaction of hydrocarbon and oxygen vapors are simulated. The results are presented as Johnson and Ettinger attenuation factors alpha (predicted indoor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
171
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(178 citation statements)
references
References 39 publications
7
171
0
Order By: Relevance
“…Based on the evidences provided by the above-mentioned empirical studies, U.S.EPA (2015a) suggested that additional investigation may be not necessary when the source to building vertical separation distance is greater than 1.8 m (6 ft) for dissolved contamination or 4.6 m (15 ft) for light non-aqueous phase liquid (LNAPL). Furthermore, results from numerical (Hers et al, 2000;Abreu and Johnson, 2006;Abreu et al, 2009;Knight and Davis, 2013;Hers et al, 2014) and analytical models (DeVaull, 2007;Yao et al, 2014;Verginelli and Baciocchi, 2014;Yao et al, 2016) were consistent with the empirical exclusion distance values reported above, showing that, in nearly all cases, a source to building vertical separation distance greater than 2 m or 5 m is sufficient to attenuate to acceptable risk-based levels petroleum hydrocarbon vapors from dissolved-phase or LNAPL sources, respectively.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Based on the evidences provided by the above-mentioned empirical studies, U.S.EPA (2015a) suggested that additional investigation may be not necessary when the source to building vertical separation distance is greater than 1.8 m (6 ft) for dissolved contamination or 4.6 m (15 ft) for light non-aqueous phase liquid (LNAPL). Furthermore, results from numerical (Hers et al, 2000;Abreu and Johnson, 2006;Abreu et al, 2009;Knight and Davis, 2013;Hers et al, 2014) and analytical models (DeVaull, 2007;Yao et al, 2014;Verginelli and Baciocchi, 2014;Yao et al, 2016) were consistent with the empirical exclusion distance values reported above, showing that, in nearly all cases, a source to building vertical separation distance greater than 2 m or 5 m is sufficient to attenuate to acceptable risk-based levels petroleum hydrocarbon vapors from dissolved-phase or LNAPL sources, respectively.…”
Section: Introductionsupporting
confidence: 79%
“…Indeed, moving laterally from the vapor source, the oxygen demand is likely to progressively decrease with a resulting enhancement of vapor attenuation due to aerobic biodegradation. Numerical simulations carried out by Abreu (2005) and Abreu and Johnson (2006) supported this assumption, showing that, for a vapor source of 200 mg/L, relatively short source-building lateral separation distances (e.g. 5-10 m) may lead to a vapor attenuation of several orders of magnitude higher than the ones achieved for a source located directly below the building.…”
Section: Introductionmentioning
confidence: 92%
“…The presence of CO 2 and methane suggests that a significant degradation of organic compounds occurs above the NAPL lens. Degradation of VOC in the unsaturated zone has been shown at several sites(Pasteris et al, 2002;Abreu and Johnson, 2006; Johnston et al, 2007; Davis et al, 2009).However, depending on permeability of the unsaturated zone, there is a competition between diffusion and degradation leading to variable amounts of VOCs remaining and CO 2 or methane produced. Due to the fine material present, which has a high tortuosity, the diffusion of VOCs is slowed down and therefore the biodegradation is quite efficient above the LNAPL lens at this site.…”
mentioning
confidence: 99%
“…Degradation of vapour-phase VOCs in landfill cover system also plays a significant role in reducing the emission amount of vapour-phase VOCs to the atmosphere (Eganhouse et al 2001;Abreu and Johnson 2006;Verginelli and Baciocchi 2011;Su et al 2015). Eganhouse et al (2001) demonstrated that degradation is the process primarily responsible for the observed attenuation of the VOCs at a municipal solid waste landfill site.…”
Section: Introductionmentioning
confidence: 99%